2022
DOI: 10.3390/ijerph19106236
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Postpartum Pelvic Girdle Pain and Pelvic Floor Muscle Function, Diastasis Recti and Psychological Factors—A Matched Case-Control Study

Abstract: There is uncertainty regarding the association between abdominal morphology, pelvic floor function, and psychological factors in women with postpartum pelvic girdle pain (PGP). The aim of this case-control study was to evaluate the differences between women with and without persistent PGP regarding pelvic floor function, diastasis recti, and psychological factors 6–24 weeks postpartum. Pelvic floor manometry, palpation examination of abdominal muscles, the International Consultation on Incontinence Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Our results showed no correlation between the SF-ICIQ and LDQ scores ( r = −0.001, P = 0.977), which is consistent with a previous report that PFD is not associated with dietary irregularities. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed no correlation between the SF-ICIQ and LDQ scores ( r = −0.001, P = 0.977), which is consistent with a previous report that PFD is not associated with dietary irregularities. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Our results showed no correlation between the SF-ICIQ and LDQ scores (r = −0.001, P = 0.977), which is consistent with a previous report that PFD is not associated with dietary irregularities. 38 To verify that DRA harms the abdominal, physical, and mental health of postpartum women, we investigated the applicability of MBIS and HerQles among 150 postpartum women (Supplement 1). We found that the DRA group showed current PROs (MBIS and HerQles) that were comparable to those in the non-DRA group, which is consistent with an earlier study.…”
Section: Discussionmentioning
confidence: 99%